HORIZONTAL GENE TRANSFER (HGT) AND SPHAGNUM FALLAX: A PHYLOGENETIC LOOK INTO THE OCCURRENCE, PREVALENCE, AND IMPORTANCE OF HORIZONTAL GENE TRANSFER IN A BOG MOSS - Sink, Tyler Zachary (East Carolina University, 2020)
Horizontal gene transfer (HGT) is a biological process that involves any transmission of genetic material that isn't vertical in nature. HGT occurs frequently between prokaryotes and plays a significant role in prokaryotic evolution. This process is also known to occur between symbiotic bacteria and their eukaryotic hosts, but less is known about HGT between eukaryotes and the role that this type of transfer may play in eukaryotic evolution in general. In this study, I took 63 pre-screened HGT candidate protein sequences from the bog moss known as Sphagnum fallax and performed phylogenetic analyses for each protein sequence/family. The topologies of each constructed phylogenetic tree were studied to find evidence of HGT involving S. fallax. Twenty-three candidate sequences were classified as contaminants, 10 were considered either inconclusive or exhibited low support for transfer, and 30 sequences had adequate or better support for HGT. The potential role of the acquired genes in the evolution and adaptation of S. fallax is discussed.
Keywords: horizontal gene transfer; lateral gene transfer; Genetic transformation; Peat mosses; Genetic transcription